Urgensitas Pelatihan dan Pengembangan dalam Manajemen Sumber Daya Manusia untuk Mengembangkan Pendidikan Islam : Literature Review - Mutafi, Ali (Program Studi Pendidikan Agama Islam Fakultas Ilmu Tarbiyah dan Keguruan UNSIQ Jawa Tengah, 2025)
The aim of this research is to determine the urgency of training and development in human resource management to develop Islamic education in order to see the implications for Islamic educational institutions. This literature review research uses qualitative descriptive methods to analyze literature data. Research findings show that training and development in human resource management is absolutely necessary in order to develop Islamic education. This argument is based on the internal situation so that there is continuous improvement in quality, as well as global challenges so that the institution has good competitiveness so that it is not inferior to other institutions. Training and development by maintaining the identity of the institution, as well as paying attention to current issues. Research implications of the importance of increasing long-term human resources for the sustainability and progress of an institution. Research is expected to contribute to Islamic educational institutions in the scope of human resource management.